2019
DOI: 10.1159/000502663
|View full text |Cite|
|
Sign up to set email alerts
|

Intravesical Treatment with Electro-Mediated Administration of Mytomicin C as Prophylaxis for Intermediate and High-Risk Nonmuscle-Invasive Bladder Cancer: A Retrospective Multicenter Study

Abstract: <b><i>Background:</i></b> Topical therapy of nonmuscle-invasive bladder cancer (NMIBC) is based on immunotherapy with Bacillus Calmette-Guerin and chemotherapy administered by passive instillation, but an active drug administration achieves a better concentration of the drugs in the bladder. <b><i>Aim:</i></b> This study aimed to investigate the effectiveness of electromotive drug administration (EMDA) of mitomycin C (EMDA/MMC) in intermediate- and high-risk NMIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In the present study, EMDA/MMC proved to be a safe and effective treatment against the recurrence and progression of NMIBC after TURBT in a sample of intermediate-and high-risk patients [24]. Our present results confirm previous studies assessing the efficacy of EMDA/MMC for NMIBC treatment [18,[26][27][28][29][30]. Several investigations have shown the efficacy of chemohyperthermia for the treatment of intermediateand high-risk patients with NMIBC [31][32][33].…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, EMDA/MMC proved to be a safe and effective treatment against the recurrence and progression of NMIBC after TURBT in a sample of intermediate-and high-risk patients [24]. Our present results confirm previous studies assessing the efficacy of EMDA/MMC for NMIBC treatment [18,[26][27][28][29][30]. Several investigations have shown the efficacy of chemohyperthermia for the treatment of intermediateand high-risk patients with NMIBC [31][32][33].…”
Section: Discussionsupporting
confidence: 88%
“…The largest reported study to date evaluated 124 EMDA/MMC treatments [11][12][13][14][15][16]. Thus, this research adds to the current literature by describing patient characteristics, efficacy, and recurrence as well as progression outcomes after EMDA/MMC treatments in the largest study reported to date, as shown in Table 4.…”
Section: Discussionmentioning
confidence: 92%
“…At the end of followup, recurrence-free rates were 75, 71.4, 50, and 25% in TaG3, T1G3, CIS, and TaT1G3 + CIS patients, respectively; progression-free rate was 61%. Carando et al [15,16] reported the data of 65 patients and 112 patients affected by NMIBC that performed a complete TURBT followed by EMDA/MMC. At the end of follow-up, recurrence-free rates were 84 and 75% in 65 and 112 patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMDA protocols adopted by the various centers show slight variations, with earlier studies using a lower current amplitude of 15 mA over shorter time periods of 20 min, while most subsequent studies utilize a maximum of 20 to 23 mA of pulsed DC applied over a duration of 30 min [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. No differences in tolerability and adverse side effects were observed with the higher amplitude and longer durations.…”
Section: Pre-clinical Studies and Clinical Applications Of Emda In On...mentioning
confidence: 99%